One Small Step or One Giant Leap Towards Access to Medicines For All - O’ Farrell, Gemma (Trinity Student Medical Journal, 2008)
In December 2005, the World Trade Organisation members amended the Trade Related Aspects of Intellectual Property Rights agreement to find a solution to the problem of access to medicine. However, intellectual property provisions, as delineated in bilateral and regional free trade agreements, have the potential to undermine their purpose and success.